Power conversion efficiency enhancement using silver nanoparticle and titanium dioxide composite film for flexible titanium foil electrode of back-illuminated dyesensitized solar cell - Shamsudin, Nur Hazahsha (2022)
Power conversion efficiency (PCE) in dye-sensitized solar cells (DSSCs) is a pivotal parameter to gauge the ability to convert light energy into electricity. However, the preference of substrates is among the issues that contribute to a low PCE. While polymer substrates have been exploited as the photoelectrodes for their flexibility and transparency which allows for front illumination, high temperature is required to eliminate the polymer binder from deposited titanium oxide (TiO2) paste. The polymer substrates are unable to withstand high temperature, and as such affect the PCE with the residue of the polymer binder within TiO2 film. Herein, a flexible titanium (Ti) substrate, a metal-based material, is used to replace the polymer substrate as the photoelectrode. Inherently, back illumination through counter electrode was opted for instead of front illumination through photoelectrode, owing to the opaque characteristic of metal substrate. However, the longer distance for the light to travel via this route impeded the development of photoelectrons, and thus reducing the power conversion efficiency (PCE). Therefore, the aim of this research is to improve the PCE via back illumination method. Herein, there were two methods proposed so as to increase the PCE. The first method is by coating the counter electrode with a different volume of platinum (Pt) solution at 30 μl, 50 μl, 70 μl and 90 μl. The second method proposed was incorporation of silver nanoparticles (AgNP) prepared via solvothermal into TiO2 paste. Platinum is integrated in the counter electrode for the optimization of PCE through catalytic activity induced by Pt. It was revealed that 70 μL of Pt solution increased the PCE from 1.248 % to 5.25 %. The incorporation of AgNP into TiO2 film has been proven to improve the light absorption as compared to solely TiO2. Solvothermal, a chemical synthesis method was implemented with a varying amount of capping agent of polyvinylpyrrolidone (PVP) from 0.2 to 2.6 g to synthesize the silver nanoparticles. TEM images showed that the higher amount of PVP would result in smaller AgNPs size, while the largest AgNPs resulted from the lower amount of PVP. The absorbance of the AgNPs signified that the absorbance decreased with increasing PVP amount. From the results, the AgNP with 28.6 nm sizes was selected to be incorporated in TiO2 paste for its low agglomeration and high absorbance value. The concentration of AgNPs was thereafter, varied from 1 to 3 wt.%, incorporated into TiO2 and followed by subsequent annealing process at 450 °C to fabricate AgNP-TiO2 film. It was observed that addition of 2 wt.% concentration of AgNPs showed the highest improvement of PCE at 4.691 % from that of TiO2 film with PCE of 2.35 %. Therefore, coating the counter electrode with Pt solution by volume and adding AgNPs into TiO2 methods have been carried out by which they have been proven to improve the PCE in DSSC. With this quantification, this study provides a way in addressing a durable and wearable flexible structure of portable electrical solar source in a wide range light intensity environment.